Improving the People’s Economy During the Covid-19 Pandemic: A Policy Review on Culinary Tourism Business in Medan City - Mohammad Firman Maulana; Parianto Parianto; A Husin Tmgr (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This research aims to describe how the Government's effort in building people's economy through culinary tourism business that has been mushrooming at any corners of the city during the pandemic. The research employed qualitative method with observation, interview and document analysis as instruments for data collection. Observations were made at several culinary tourism spots following an interview session with some participants from tourism office staffs, culinary business managers and visitors. Related documents were obtained from both the Government Service and culinary business actors. The results of this research indicate that the Government's policy plays an important role in improving the community's economy as it absorbs lot of people to work in and encourages the others to supply the ‎necessary ingredients in which at the same time the business is potential to increase regional income